Chronology of Holocene storm events along the European Atlantic coast: New data from the Island of Yeu, France. (August 2018) - Pouzet, Pierre; Maanan, Mohamed; Piotrowska, Natalia; Baltzer, Agnès; Stéphan, Pierre; Robin, Marc
This paper reviews the reconstruction of European Atlantic storm events with the contribution of a new stormy reconstruction in its central part. Three marsh environments on the island of Yeu were chosen to identify disturbing storm events from the Mid- to Late Holocene with vibracore sampling, radiocarbon dating and sedimentary analysis. Nine probable intervals of high energy deposition in these low-transport-activity environments are estimated: 600–500, near 1590, 2100–1950, 2850–2350, 3500–3270, 5400–5370, 6650–6510, near 7000 and between 7670 and 7470 calibrated years before present (cal y BP). By comparison with sedimentological paleostorm studies, we confirm six European Atlantic storm events estimated at near 600–300, 1700–1100, 2900–2500, 3500–3300, 5500–5100 and 7700–7100 cal y BP, corresponding to worldwide Holocene cooling climatic periods. A comparison with other storminess reviews of worldwide main stormy coasts shows that Holocene storms can increase during global cooling periods in the northern hemisphere.